The Impact of Oral Micronutrient Interventions on Hemoglobin Concentration in Anemic Women of Childbearing Age: A Review and Meta-Analysis. (14th June 2022) - Van Cor, Sara; Fuchs, Hannah; Waddel, Hannah; Chadha, Manpreet; Mehta, Christina; Moore, Reneé; Arabi, Mandana; Pachón, Helena
Abstract: Objectives: To complete a systematic review and meta-analysis of nutrition interventions conducted with anemic, non-pregnant women of childbearing age to determine their impact on hemoglobin concentration (Hb). Methods: Seventeen online databases were searched from November 14-December 14, 2020. Two reviewers independently screened documents via Covidence. Inclusion criteria were English-language studies; longitudinal intervention studies, including non-randomized controlled trials, randomized controlled trials, and intervention trials without control groups; women anemic at baseline; and micronutrients administered orally for > 4 weeks. Data were extracted from 45 studies that met inclusion criteria. Bayesian arm-based meta-analyses estimated the mean change in hemoglobin (g/L) for several stratifying variables. Results: For all delivery methods, there was a mean increase in Hb: 17.48 g/L (95% Credible Interval (CI): 13.72, 21.03) for oral supplements, 18.34 g/L (95% CI: 12.32, 25.49) for `other' interventions (i.e., powdered leaf extract, papaya, dates, iron-cooking ingot), and 6.99 g/L (95% CI: 2.80, 11.48) for fortified food. Including iron in the nutrients administered to anemic women reliably increased their Hb. Iron alone (16.51 g/L, 95% CI: 12.53, 20.73), iron and folic acid (17.69 g/L, 95% CI: 13.25, 22.94), and multiple micronutrients including iron (16.57 g/L, 95% CI: 12.11, 21.54), all had a much larger effect on Hb change than vitamins alone (7.47 g/L, 95% CI: −0.73, 16.01). Intervention duration did not have a large effect on mean Hb change as a 4–16-wk duration increased Hb by 17.49 g/L (95% CI: 13.07, 21.64), a 17–28-wk duration increased Hb by 13.23 g/L (95% CI: 5.53, 20.18) and a > 52-wk duration increased Hb by 17.9 g/L (95% CI: 9.78, 24.91). Conclusions: The nutrient-delivery method and inclusion of iron modified the Hb changes observed in anemic women, while intervention duration did not. Specifically, supplements, 'other' interventions, and iron-cooking ingots were more effective in raising Hb than fortified food; any intervention which included iron increased mean Hb compared to those with only vitamins; and the effect of interventions on mean Hb did not differ by study duration. Funding Sources: Global Affairs Canada.